Expanding the Spectrum of Movement Disorders Associated With C9orf72 Hexanucleotide Expansions - Estevez-Fraga, Carlos (Neurol Genet, 2021)
OBJECTIVE: Hexanucleotide repeat expansions (HREs) in C9orf72 are a major cause of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS). We aimed to determine the frequency and phenomenology of movement disorders (MD) in carriers of HRE in C9orf72 through a retrospective review of patients' medical records. METHODS: We retrospectively reviewed the clinical records of patients carrying a C9orf72 HRE in the pathogenic range and compared the characteristics of patients with and without MD. RESULTS: Seventeen of 40 patients with a C9orf72 HRE had a documented MD. In 6 of 17, MD were the presenting symptom, and in 2 of 17, MD were the sole manifestation of the disease. FTD was present in 13 of 17 patients, ALS in 5 of 17 patients, and 2 of 17 patients did not develop FTD or ALS. Thirteen of 17 patients had more than one MD. The most common MD were parkinsonism and tremor (resembling essential tremor syndrome), each one present in 11 of 17 patients. Distal, stimulus-sensitive upper limbs myoclonus was present in 6 of 17 patients and cervical dystonia in 5 of 17 patients. Chorea was present in 5 of 17 patients, 4 of whom showed marked orofacial dyskinesias. The most frequent MD combination was tremor and parkinsonism, observed in 8 of 17 patients, 5 of whom also had myoclonus. C9orf72 patients without MD had shorter follow-up times and higher proportion of ALS, although these results did not survive the correction for multiple comparisons. CONCLUSIONS: MD are frequent in C9orf72. They may precede signs of ALS or FTD, or even be present in isolation. Parkinsonism, tremor, and myoclonus are most commonly observed.